MANFAAT WISATA TUGU KEBULATAN PROKLAMASI DI RENGASDENGKLOK KARAWANG BAGI MASYARAKAT LOKAL SEBAGAI PELUANG USAHA UNTUK MENINGKATKAN TARAF HIDUP SEBAGAI PEDAGANG KECIL. - Retnosary, Rieke (LPPM Universitas Buana Perjuangan Karawang, 2017)
Abstrak Tugu Kebulatan Proklamasi (TKP) as a destination of heritage tourism in Rengasdengklok, Karawang, has given opportunity to many local residents to increasing their income for better family economic. Researcher found in observed that characteristic of small business from TKP area was on food bussiness and cloths. In holiday time, many small traders (pedagang kecil) for the local visitor or tourism was offered besides food, small traders such as toys for children and other specification of children’s game. But for this research, researcher just focus on local or ordinary foods. Small traders offering the local food and ordinary food, like gorengan, mie ayam, bakso, es kelapa, and serabi, ordinary drink like, coffee and other thing that they can offer. Some time they (as a small traders) offer the mie ayam and provided the drink too, such as tea or mineral water and so on. Five (5) small traders which interviewed feel the positive impact from the existences of TKP. From five (5) small traders, their income were between Rp 3,000,000 until 9,000,000 per month, the average of their income was Rp 5,800,000. This income very convenience for local residents if they want to take food for business. According to the mandate of article (pasal) 31 paragraph (ayat) (4) number of law 10 in 2009 about the tourism, that the aim of tourism is to increase economic growth and people welfare. With tourism, people or local resident could increase with many opportunity for small economic problems. Key words: TKP Tourism, opportunity, local residents, increase income, positive impact, small traders, economic growth.